Comparison of Mechanical Thrombectomy with Contact Aspiration, Stent Retriever, and Combined Procedures in Patients with Large-Vessel Occlusion in Acute Ischemic Stroke - Procházka, Václav; Jonszta, Tomas; Czerny, Daniel; Krajca, Jan; Roubec, Martin; Hurtikova, Eva; Urbanec, Rene; Streitová, Dana; Pavliska, Lubomir; Vrtková, Adéla (Medical Science Monitor, 2018)
BACKGROUND We investigated the properties and effects of 5 mechanical thrombectomy procedures in patients with acute ischemic stroke. The relationships between the type of procedure, the time required, the success of recanalization, and the clinical outcome were analyzed. MATERIAL AND METHODS This prospective comparative analysis included 500 patients with acute ischemic stroke and large-vessel occlusion. We compared contact aspiration thrombectomy (ADAPT, n=100), stent retriever first line (SRFL, n=196), the Solumbra technique (n=64), mechanical thrombectomy plus stent implantation (n=81), and a combined procedure (n=59). RESULTS ADAPT provided shorter procedure (P<0.001) and recanalization times (P<0.001) than the other techniques. Better clinical outcome was achieved for ischemia in the anterior circulation than ischemia in the posterior fossa (P<0.001). Compared to the other techniques, patients treated with ADAPT procedure had increased odds of achieving better mTICI scores (P=0.002) and clinical outcome (NIHSS) after 7 days (P=0.003); patients treated with SRFL had increased odds of achieving better long-term clinical status (3M-mRS=0-2; P=0.040). Patients with SRFL and intravenous thrombolysis (IVT) had increased odds of better clinical status (3M-mRS=0-2; P=0.031) and decreased odds of death (P=0.005) compared to patients with SRFL without IVT. The other treatment approaches had no additional effect of IVT. Patients with SRFL with a mothership transfer had increased odds of achieving favorable clinical outcome (3M-mRS) compared to SRFL with the drip-and-ship transfer paradigm (P=0.015). CONCLUSIONS Our results showed that ADAPT and SRFL provided significantly better outcomes compared to the other examined techniques. A mothership transfer and IVT administration contributed to the success of the SRFL approach.
Keywords: trombolytická terapie; výsledek terapie; Mechanical Thrombolysis; mechanická trombolýza; Male; Middle Aged; ischemie; cévní mozková příhoda; trombektomie; Stroke; Stents; Aged; Prospective Studies; mužské pohlaví; senioři; ischemie mozku; Ischemia; Thrombolytic Therapy; Treatment Outcome; lidé; ženské pohlaví; Humans; stenty; Female; lidé středního věku; Thrombectomy; Brain Ischemia; prospektivní studie